Tool wear and hole quality evaluation in cryogenic Drilling of Inconel 718 superalloy. (March 2020) - Khanna, Navneet; Agrawal, Chetan; Gupta, Munish Kumar; Song, Qinghua
Abstract: In this paper, the research effforts have been made to discover the potential of cryogenic machining as a sustainable manufacturing process for drilling of Inconel 718 superalloy. The drilling performance is investigated in terms of thrust force, torque, tool wear, chip morphology and hole quality (circularity - CIR, cylindricity – CYL, and surface roughness - R a values). The experimental result shows temperature-dependent tool wear drastically reduced under cryogenic drilling as compared to dry drilling, and this leads to a reduction in torque values up to 30%. Furthermore, the cryogenic drilling improves tool life up to 87.50% and produce better quality holes due to a decrease in CIR deviations (up to 51%), CYL deviations (up to 77%), and R a values (up to 48%). Highlights: Detailed tool wear analysis under dry and cryogenic drilling using FESEM and EDS. Cryogenic drilling of Inconel 718 improves tool life as compared to dry drilling. Cryogenic drilling improves hole quality in terms of CIR & CYL deviations and R a values. Better chip morphology and lower torque values are observed under cryogenic drilling.